2015
DOI: 10.1002/pola.27656
|View full text |Cite
|
Sign up to set email alerts
|

A benign initiating system for cationic polymerization of isobutyl vinyl ether: Silver salt/aryl(alkyl) halide/lewis base

Abstract: Aryl(alkyl) halides and silver salts were studied as environmentally benign initiating systems for cationic polymerization of isobutyl vinyl ether (IBVE). The reactivity of the benzyl cations could be effectively controlled by using dimethyl sulfide (Me2S) as an additive, which was shown to be an effective Lewis base (LB), and diethyl ether as a reaction solvent. Detailed study of various benzyl cations and the order of addition of the reagents revealed that the reaction was controlled by the electronic and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The cationic polymerizations of three VEs using the AgClO 4 /Ph 2 CHBr/dialkyl sulfide initiating system were examined. We have previously shown that IBVE is polymerized cationically in a highly controlled manner in the presence of Me 2 S . In Table , the effect of temperature and sulfides on the polymerization of IBVE is shown.…”
Section: Resultsmentioning
confidence: 62%
See 4 more Smart Citations
“…The cationic polymerizations of three VEs using the AgClO 4 /Ph 2 CHBr/dialkyl sulfide initiating system were examined. We have previously shown that IBVE is polymerized cationically in a highly controlled manner in the presence of Me 2 S . In Table , the effect of temperature and sulfides on the polymerization of IBVE is shown.…”
Section: Resultsmentioning
confidence: 62%
“…The drastic changes in conversion and MWD are attributed to the different coordination ability of these sulfides; the basicity of PhSMe is lower than Me 2 S owing to the resonance effect of phenyl group, and the steric hindrance is another important factor. However, using the similar polymerization conditions (Entry 1), the cationic polymerization of IBVE, a more active monomer than p MOS, proceeded smoothly to reach quantitative conversion in 30 min . These results suggested that the polymerization of more active monomer, VE, was relatively unaffected by the AgClO 4 /BnBr/Me 2 S initiating system.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations